GEOCHEMICAL PROVENANCE AND SPATIAL VARIATION OF FLUORIDE IN GROUNDWATER OF SINDHUDURG DISTRICT, WESTERN MAHARASHTRA - Suneetha, N.; Gupta, G.; Shailaja, G. (International Journal of Research -GRANTHAALAYAH, 2018)
The present study focuses on the occurrence and intensity of fluoride in drinking water from the Malvan-Vijaydurg coastal tract in Sindhudurg district, Maharashtra. Concentration of fluoride (F-) from 36 dug wells/bore wells sampled during this study ranged from 0.04 mg/L to 1.6 mg/L. The results indicate that about 47% of the water samples from the study area have fluoride content greater than 1 mg/L, which exceeds the permissible limit of BIS (1 mg/L), while 4 samples exceeded the World Health Organization standards of 1.5 mg/L. Spatial variation in F- concentration indicates that most of the sampling sites having comparatively high fluoride also have high values of pH, EC and TDS concentration measured in groundwater. High fluoride levels are associated with Ca-Mg-Cl-SO4, Na-Cl and Na-HCO3 type water produced by calcite precipitation and/or base ion exchange. The groundwater with higher fluoride concentrations is accompanied by lower Ca+2 levels. This study augments our understanding on geochemical behaviour of F- concentration and highlights the importance of spatial variability of F- in coastal aquifers. It is also pertinent to monitor the water quality periodically in this region and consequently discontinue using the wells which contain high fluoride concentration.